The Role of Leadership in Change in Healthcare Facilities: A Qualitative Study - Wanser , Latoya; Luckel , Henry (American Journal of Management, 2021)
Change is inevitable in all areas of business today. Studies have shown that the majority of change within organizations fails to achieve the desired results more than those changes succeed. Articles focusing on the effect leadership has on the success or failure of change efforts is lacking. The participants for this study included healthcare professionals working in leadership positions. Data was collected through the use of individual, standardized, and open-ended questions. The findings of this study reveal that leaders in healthcare have the knowledge to implement change using change management principles but still lack the ability to influence cultural change.